Promotion of K3 in the Informal Sector of Occupational Diseases (PAK) and Occupational Diseases (PAHK) in the Workplace - Octavianus Hutapea; Moch Sahri; Puspita Dwi Kartikasari; Yeni Dwi Puspitasari; Zulfi Ahmad Ruhansyah; Aldin Taufal Alufti; Amanda Nabila Maharani Irawan (Journal of Health Community Service, 2024)
In the midst of rapid industrial development, small and medium enterprises such as welding factories play an important role in improving the welfare of the community. Jagiru Wonokuromo No. 326, Jagiru, stingy. Workplace Safety Factory workers are often at risk of accidents due to the use of heavy equipment and welding. Promoting workplace safety practices reduces accidents and helps workers understand the importance of self-protection. This improves the functionality and quality of the product. Jagir Jaya's interaction in the welding workplace is expected to have a positive impact on maintaining occupational safety and health, increasing awareness, and preventing accidents that can threaten worker safety. Socialization in the welding workplace has a significant impact on maintaining worker safety and health. Therefore, increasing safety awareness in the target area will help workers understand the risks associated with the welding process such as fire hazards, smoke, and heavy equipment. With a better understanding, workers tend to be more careful and pay more attention to safety procedures. Emergency training is also conducted during placement to train employees in responding to emergencies such as fires and accidents. Knowledge of evacuation procedures and the use of fire extinguishers can save lives.